Efektivitas Model Discovery Learning Berbantuan Smartphone-Based Sensor (Phyphox) terhadap Pemahaman Konsep Mahasiswa pada Materi Medan Magnet - Ary Analisa Rahma; Hermin Arista; Utami Ratna Swari (Jurnal Pustaka Cendekia Pendidikan, 2026)
Magnetic field material is identified as difficult for students to understand due to the level of conceptual abstraction and the complexity of the mathematical representations involved. This study aims to analyze the effectiveness of a discovery learning model assisted by a smartphone-based sensor (Phyphox) on students’ conceptual understanding of magnetic field material. This study involved twenty-seven electrical engineering students using a test instrument consisting of 20 multiple-choice questions. The results of the independent sample t-test using SPSS 26 yielded a calculated t-value of 6.803, indicating a significant difference in physics concept understanding regarding magnetic field material between the two research classes. The improvement in students’ conceptual understanding of magnetic field material in the experimental class was in the high category, with an average N-Gain value of 70.964. Thus, it can be concluded that discovery learning assisted by the Phyphox application is more effective in improving students’ conceptual understanding of magnetic field material.